2020
DOI: 10.1111/maps.13431
|View full text |Cite
|
Sign up to set email alerts
|

Determining the age and possibility for an extraterrestrial impact formation mechanism of the Ilumetsa structures (Estonia)

Abstract: The Ilumetsa site, in Estonia, consists of two round, rimmed structures that are 725 m apart. The structures are listed as proven impact craters in the Impact Earth database, despite lack of commonly accepted, unequivocal proof of extraterrestrial collision identified at this location. We excavated trenches though the Ilumetsa Large and Ilumetsa Small structures and found small pieces of charcoal within the putative proximal ejecta in both structures, in a similar geological setting as previously identified ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…We selected charcoal particles from different locations within both trenches to ensure that a full variability within data is represented. The samples came from the deepest sections of the zones to minimize contamination from any potential surface charcoal, similar to what occurred for some of the samples from Ilumetsa (Losiak et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected charcoal particles from different locations within both trenches to ensure that a full variability within data is represented. The samples came from the deepest sections of the zones to minimize contamination from any potential surface charcoal, similar to what occurred for some of the samples from Ilumetsa (Losiak et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…3). We selected the positions and lengths of the trenches based on our previous field experience with other small impact craters developed in unconsolidated materials (see Losiak et al., 2016, 2020) and based on a literature review (Herd et al., 2008; Szokaluk et al., 2019). Tor 1 (3.0 m long and up to 1.2 m deep) was located on the northern side of the structure, where the outer slopes were the steepest; it started at the base of the slope and continued until halfway to the rim crest.…”
Section: Methodsmentioning
confidence: 99%
“…The blast wave can also carry off excess heat, preserving interior organic materials, as observed in extraterrestrial samples of all sizes [e.g., Murchison (Pizarello et al, 1991); Tagish Lake (Brown et al, 2000); micrometeorites (Glavin and Bada, 2001)]. Additional opportunities for survival of organics include lower shock pressures experienced during impact into a porous target (e.g., Wünnemann et al, 2005); the decay of peak shock pressure during impact into water (e.g., Artemieva and Shuvalov, 2002;Artemieva and Pierazzo, 2011); and smaller impacts that experience only short-lived thermal anomalies (e.g., Losiak et al, 2020). Fragmentation can also allow survival of organic materials because it enables a deceleration in velocity (e.g., Artemieva and Pierazzo, 2009) and allows ablation to act over a much larger surface area (Mehta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An impact site with more than one distinct crater. Common Rare Impact crater strewn fields are a group of structures formed at the same time (e.g., Losiak et al, 2018Losiak et al, , 2020 by a disruption of a single asteroid during its atmospheric entry (Bland and Artemieva, 2006).…”
Section: Rare Yes and Nomentioning
confidence: 99%
“…Pieces of achondrites can be nearly as resistant to weathering as terrestrial rocks, but once they lose the fusion crust, they may be very hard to recognise from the surrounding material (especially in the post-glacial areas where a wide variety of rock types are present). This may potentially explain the formation of Ilumetsa (Losiak et al, 2020) and Sobolev (Khryanina, 1981) structures that have properties consistent with them being formed by an impact of an asteroid, but where no clear signs of extraterrestrial material was identified. Currently both of those features are classified as potential impact craters (see section 5.3).…”
Section: The Challenge Of Small Cratersmentioning
confidence: 99%